2003
DOI: 10.1086/368290
|View full text |Cite
|
Sign up to set email alerts
|

Parental Effects in a Partially Self‐Incompatible HerbCampanula rapunculoidesL. (Campanulaceae): Influence of Variation in the Strength of Self‐Incompatibility on Seed Set and Progeny Performance

Abstract: We employ a full reciprocal diallel design between 10 parental plants that differed in their strength of self-incompatibility (SI; strong, intermediate, and weak) to examine parental effects on seed set and 10 components of fitness of progeny performance in Campanula rapunculoides. We perform ANOVAs to separate the influence of the strength of SI and the identity of the maternal and paternal parent on family performance. We calculate the phenotypic and genetic correlations between traits to determine potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 100 publications
3
7
0
Order By: Relevance
“…For example, we have shown that the strength of SI has a heritable genetic basis (Good-Avila and Stephenson, 2002), that strong and weak SI families differ in inbreeding depression for vegetative traits (Vogler et al, 1999b) and show differential performance as pollen and seed parents (Good-Avila and Stephenson, 2003), and here, we have shown that strong and weak families have differential reproductive output through both male and female function. For example, we have shown that the strength of SI has a heritable genetic basis (Good-Avila and Stephenson, 2002), that strong and weak SI families differ in inbreeding depression for vegetative traits (Vogler et al, 1999b) and show differential performance as pollen and seed parents (Good-Avila and Stephenson, 2003), and here, we have shown that strong and weak families have differential reproductive output through both male and female function.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…For example, we have shown that the strength of SI has a heritable genetic basis (Good-Avila and Stephenson, 2002), that strong and weak SI families differ in inbreeding depression for vegetative traits (Vogler et al, 1999b) and show differential performance as pollen and seed parents (Good-Avila and Stephenson, 2003), and here, we have shown that strong and weak families have differential reproductive output through both male and female function. For example, we have shown that the strength of SI has a heritable genetic basis (Good-Avila and Stephenson, 2002), that strong and weak SI families differ in inbreeding depression for vegetative traits (Vogler et al, 1999b) and show differential performance as pollen and seed parents (Good-Avila and Stephenson, 2003), and here, we have shown that strong and weak families have differential reproductive output through both male and female function.…”
Section: Discussionsupporting
confidence: 58%
“…In C. rapunculoides, we have now accumulated considerable evidence that variation in the strength of SI among individuals may be of evolutionary importance. For example, we have shown that the strength of SI has a heritable genetic basis (Good-Avila and Stephenson, 2002), that strong and weak SI families differ in inbreeding depression for vegetative traits (Vogler et al, 1999b) and show differential performance as pollen and seed parents (Good-Avila and Stephenson, 2003), and here, we have shown that strong and weak families have differential reproductive output through both male and female function. The strong influence of variation in self-fertility on reproductive success has certainly strengthened our ability to detect associations between genetic load and modifiers of SI.…”
Section: Discussionsupporting
confidence: 58%
“…We also found a significant maternal effect on the time to seedling emergence (about 25% of the V P ), though not as high as for seed mass. Similarly strong maternal effects are commonly reported for other species in seed size (Antonovics and Schmitt 1986;Mazer 1987b;Schwaegerle and Levin 1990;Biere 1991a;Platenkamp and Shaw 1993;Montalvo and Shaw 1994;Schmid and Dolt 1994;Waser et al 1995;Wolfe 1995;Helenurm and Schaal 1996;Byers et al 1997;Lipow and Wyatt 1999), seed numbers (Mazer 1987b;Waser et al 1995;Good-Avila and Stephenson 2003), and time to germination (Biere 1991a;Platenkamp and Shaw 1993;Schmid and Dolt 1994;Helenurm and Schaal 1996), including the columbine Aquilegia caerulea (Montalvo and Shaw 1994). The importance of maternal effects in these traits is hardly surprising, because seeds develop surrounded and provisioned by maternal tissue and, in addition, the genetic contribution of mothers to seeds is higher compared to that of fathers.…”
Section: Maternal Effects In Traditional Mean Trait Valuessupporting
confidence: 55%
“…In studies that used more than one discrete inbred group, some study traits (37 in total) only differed in f (e.g. Good‐Avila & Stephenson, ; see Table ), therefore potentially creating some pseudo‐replication. However, models fitted to data sets that comprised mean B across each set of study traits that differed only in f yielded similar results (not shown).…”
Section: Resultsmentioning
confidence: 99%